Flood risk pattern recognition by using environmetric technique: A case study in langat river basin - Saudi A.S.M.; Juahir H.; Azid A.; Toriman M.E.; Kamarudin M.K.A.; Mustafa A.D.; Amran M.A.; Madihah Mohd Saudi (Penerbit UTM Press, 2024)
Indexed by Scopus